1993
DOI: 10.1063/1.109205
|View full text |Cite
|
Sign up to set email alerts
|

High-mobility p-channel metal-oxide-semiconductor field-effect transistor on strained Si

Abstract: An enhancement-mode p-channel metal-oxide-semiconductor field-effect transistor (PMOSFET) is fabricated on a strained Si layer for the first time. A biaxial strain in a thin Si layer is produced by pseudomorphically growing this layer on a Ge0.25Si0.75 buffer layer which is grown on a Si substrate. At higher magnitude of gate bias, channel mobility of a strained Si PMOSFET has been found to be 50% higher than that of an identically processed conventional Si PMOSFET.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(35 citation statements)
references
References 11 publications
0
35
0
Order By: Relevance
“…First experiments have demonstrated a hole mobility enhanced by 50 % compared to the equivalent p-MOSFET device. [78,79] In conclusion, the performance demonstrated experimentally by Si 1±x Ge x MODFETs and predicted for heterostructure and strained-Si CMOS is extremely impressive and has the ability to compete at least in terms of speed with some of the III±V technologies. Until a high quality, low defect density virtual substrate or bulk Si 1±x Ge x substrates are available, the technology will be confined to the research laboratories or small-volume niche applications.…”
Section: Applications Using Virtual Substratesmentioning
confidence: 92%
“…First experiments have demonstrated a hole mobility enhanced by 50 % compared to the equivalent p-MOSFET device. [78,79] In conclusion, the performance demonstrated experimentally by Si 1±x Ge x MODFETs and predicted for heterostructure and strained-Si CMOS is extremely impressive and has the ability to compete at least in terms of speed with some of the III±V technologies. Until a high quality, low defect density virtual substrate or bulk Si 1±x Ge x substrates are available, the technology will be confined to the research laboratories or small-volume niche applications.…”
Section: Applications Using Virtual Substratesmentioning
confidence: 92%
“…Early in the 70s, theorists predicted that suitably structured superlattices of two indirect bandgap semiconductors could produce a direct bandgap material through proper folding of the Brillouin zone [6,8,9], which when applied to Si and Ge, will be the ultrathin Sim-Gen (m + n = 10) superlattices. In the early work on this subject, Pearsall et al [1][2][3][4][5][6][7][8][9][10]11] observed features in their electroreflectance measurements at energies theoretically predicted for pseudodirect optical transitions in the superlattices grown on Ge buffer. Further studies [13,14] on similar samples by stress-modulated reflectance (or piezoreflectance) have identified that the low energy structures at energies above the Ge direct bandgap are due to quantum confined direct transitions from the Ge spacer region rather than from the pseudo-direct bandgap Sim-Gen superlattices.…”
Section: Optical Properties Of As-grown Heterostructuresmentioning
confidence: 99%
“…The current research on this subject focuses on two aspects, i.e. electron transport [1][2][3][4] and optical characterization of structures aiming at possible cheap Si-based optoelectronic devices technologically compatible with the widely spread industrial use of silicon technology [5][6][7]. Most of the recent work on the optical properties of Si-Sia_xGex and Si-Ge low dimensional structures are based on molecular beam epitaxial (MBE) or metal-organic chemical vapour deposition (MOCVD) grown 2D ultrathin Sim-Ge, superlattices with (m + n) = 10, in which system the possibility of achieving pseudodirect bandgap was predicted in theory [6,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…This motivates the search for alternative materials and new device structures to boost the device performance. Strained Si epitaxially grown on relaxed SiGe provides enhanced electron and hole mobilities compared to bulk Si because of the modification of the band structure by in-plane tensile strain [1,2]. It has been shown that the performance of 40 nm gate length MOSFETs was significantly improved using strained Si [3].…”
Section: Introductionmentioning
confidence: 98%